YouTube as a Source of Authentic Economic Discourse for ESP Learners: A Study on BBC News Videos - Fitria, Tira Nur; Afdaleni (ITB AAS Indonesia Surakarta, 2025)
This research explores how YouTube can be used as a source of authentic economic discourse for English for Specific Purposes (ESP) learners, particularly in the field of economics. The official BBC News website could be accessed at https://www.bbc.com/news, which provided additional economic news articles and related video content for reference. This study used a descriptive qualitative approach to examine how BBC News economic videos on YouTube can serve as authentic materials for ESP in economics. Authentic materials, such as news reports, company documents, and interviews, present language in its natural form and expose learners to real professional discourse, vocabulary, and cultural nuances often absent in textbooks. Data were collected from BBC News economic content available on its YouTube channel and official website, providing credible, up-to-date coverage of topics like inflation, trade, and cryptocurrency. Findings indicate that integrating these videos into ESP instruction bridges classroom learning with workplace communication, enabling learners to develop both language proficiency and subject knowledge. A structured pre-viewing, while-viewing, and post-viewing framework supports comprehension and application through vocabulary preparation, active listening, and interactive follow-up tasks. The analysis identified six benefits: (1) rich vocabulary in context, (2) multimodal learning through narration, visuals, and data, (3) real-world relevance, (4) enhanced listening and critical thinking, (5) cultural and professional discourse awareness, and (6) integration of language and content following CLIL principles. The diversity of economic topics ensures exposure to various professional communication styles, making BBC News economic videos a valuable tool for developing vocabulary, comprehension, analytical skills, and professional communication abilities in economics-focused ESP learners.